PENGARUH MARKETING MIXTERHADAP KEPUTUSAN KONSUMEN BERBELANJA PADA PASAR MODERN CARREFOUR PANAKKUKANG SQUARE Di Kota Makassar - Sumarni Sumarni (Jurnal Mirai Management, 2020)
This study aims to determine the effect of marketing mix (product, price, place, promotion) on consumers' decisions to shop on the modern market (Carrefour) in Makassar City. This study uses 100 respondents and data collection uses the questionnaire method. The method of data analysis uses the SPSS version 17 program for multiple linear regression analysis. Based on the results of research using the t-test it is known that all Marketing Mix variables (products, prices, places and promotions) have a positive and partially significant effect on Consumer Shopping Decisions in the Carrefour Panakukang Square Modern Market in Makassar City. Based on the f test (simultaneous) it is known that F of 361,393> of F 3.09 which means all independent variables Marketing Mix (Product, Price, Place, Promotion) simultaneously or jointly have a positive and significant effect on the dependent variable (Consumer Shopping Decision ) in the Carrefour Panakkukang Square modern market in Makassar City